Libertà religiosa in Romania durante la pandemia del virus Covid-19: La situazione della Chiesa ortodossa rumena - Grigoriþã, Georgicã (Salute umana e tradizioni religiose di fronte alle emergenze sanitarie, 2021)
With the onset of the Covid pandemic, Romania took the necessary measures to combat it, and some of the measures affected religious freedom in general and the exercise of Orthodox liturgical worship in particular. In this context, the Romanian Orthodox Church had an assumed and balanced attitude, focused on the rights of Orthodox believers, thus supporting both the fundamental right to exercise religious freedom and health measures taken by public authorities to prevent and combat the Covid-19 pandemic. Of course, in this process, there were some difficult situations, which were solved through dialogue and cooperation in a spirit of mutual respect.